The Roots of Islamist Armed Struggle, 1968-2007 - Tim Krieger; Daniel Meierrieks (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This contribution studies the influence of poor politico-economic factors, unfavorable demographic conditions, state failure, modernization, secularization, globalization and the perceived dependency of the Islamic world from the West on the onset of armed Islamist activity for 155 countries between 1968 and 2007. Its empirical findings show that the onset of militant Islamism is robustly associated with the discrimination of Islamic minorities, state weakness, the presence of large (secular and possibly predatory) governments, military dependence from the U.S., external cultural influences and the availability of a large pool of potential recruits (as indicated by a large, Muslim population). Poor economic conditions, modernization and authoritarianism share no association with the onset of Islamist militancy. The latter findings imply that democratic reforms and economic development while often advocated countering Islamist violence appear to be rather ineffective tools of conflict prevention.
Keywords: D74; H56; N40; 330